Parental Attachment and Peer Support as Predictors of Adolescents’ Psychological Well-Being at X Junior High School, Yogyakarta - Alfarina, Ria; Jannah, Raudhatul (Fathana, 2025)
This study predicts the role of parental attachment and peer support in adolescent psychological well-being among students at SMP "X" Yogyakarta. The participants consisted of 181 students, the majority aged 14 and 15 years. The research employed a quantitative method with multiple linear regression analysis. The instruments used in this study were the Inventory of Parent and Peer Attachment (IPPA) to measure attachment, the Social Support Questionnaire for Children (SSQC) to assess peer social support, and an adolescent psychological well-being scale. The results showed that parental attachment and peer support significantly predicted psychological well-being (F = 9.14, p < 0.001, R = 0.138). Further analysis revealed differences in psychological well-being based on class, age, and gender. The implications of this study highlight the importance of parental and peer roles in enhancing adolescents’ psychological well-being through fostering positive relationships and strong social support. This research provides a foundation for developing interventions aimed at improving adolescent psychological well-being by strengthening social and family relationships.